Biodiversity of the Gulf of Guinea Oceanic Islands 2022
DOI: 10.1007/978-3-031-06153-0_18
|View full text |Cite
|
Sign up to set email alerts
|

The Amphibians of the Gulf of Guinea Oceanic Islands

Abstract: This chapter reviews the diversity, evolutionary relationships, ecology, and conservation of the Gulf of Guinea oceanic islands’ endemic caecilian and anuran fauna. A total of nine amphibian species (representing five families) are known from São Tomé and Príncipe islands, all of which are endemic. No amphibians have been reported from Annobón. Taxonomic research on this group of animals began in the second half of the nineteenth century with subsequent refinement following the advent of molecular techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Chapter 17 (Costa et al 2022) lists and discusses the more than 1000 species of fishes that potentially occur in the fresh and marine waters of the islands. Chapter 18 (Bell et al 2022) deals with amphibians, which include three species on Príncipe and six on São Tomé, all of which are endemic (Annobón has no amphibians). The chapter provides a detailed overview of species biology, ecology, and biogeography.…”
Section: Book Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Chapter 17 (Costa et al 2022) lists and discusses the more than 1000 species of fishes that potentially occur in the fresh and marine waters of the islands. Chapter 18 (Bell et al 2022) deals with amphibians, which include three species on Príncipe and six on São Tomé, all of which are endemic (Annobón has no amphibians). The chapter provides a detailed overview of species biology, ecology, and biogeography.…”
Section: Book Structurementioning
confidence: 99%
“…Chapter 25 (Ayres et al 2022) assesses recent strategies of formal and non-formal environmental education on São Tomé and Príncipe, which are vital to augment local capacity for conservation and scientific research. Chapter 26 (Bell et al 2022) proposes a path toward biodiversity resilience for future naturalists, biologists, conservationists, and educators.…”
Section: Book Structurementioning
confidence: 99%
“…This project, which has made a total of 12 expeditions to the islands as of 2020, is still ongoing and has been one of the most comprehensive efforts to study the biodiversity of São Tomé and Príncipe islands since Francisco Newton's expedition in the nineteenth century. Due to Drewes' herpetological background, the project has always had a strong emphasis on the study of the amphibians and reptiles of these islands (see Bell et al 2022). The reptile collections resulting from these expeditions are currently the largest in the world (Table 19.1), with a total of 449 specimens (Scheinberg and Fong 2019).…”
Section: History Of Reptile Researchmentioning
confidence: 99%
“…The genus Afrotyphlops is represented by the Príncipe endemic Afrotyphlops elegans (Peters, 1868), locally known as "Cobra-bobô" (Fig. 19.2, 5), which is the same name used on São Tomé to refer to the endemic caecilians of the genus Schistometopum Parker, 1941 (Bell et al 2022). Not much is known about the ecology of this fossorial species, however, in multi-locus and morphological phylogenetic analyses of typhlopid snakes, Kornilios et al (2013) and Hedges et al (2014) showed that it is closely related to the Central African Afrotyphlops angolensis (Bocage, 1866).…”
Section: Squamatamentioning
confidence: 99%
“…One fundamental difference in the research carried out in the twenty-first century is the use of molecular methods to study the taxonomy, phylogenety, and biogeography of the biodiversity of the islands. While this has not yet been applied to all taxonomic groups, the use of molecular methods has been widely applied to the study of the island's herpetofauna (Bell et al 2022;Ceríaco et al 2022), birds (Melo et al 2022) and, to a lesser extent, plants (Plana et al 2004;Soares et al 2010). The growing importance of ecological and conservation studies has also marked the research landscape in the oceanic islands of the Gulf of Guinea, with dozens of works and theses produced on the topic, especially at the University of Lisbon (see , Soares et al 2022), but also the seminal works on marine turtles (see Ferreira-Airaud et al 2022), plants (see Stevart et al 2022, and even land molluscs (see Panisi et al 2022).…”
Section: Twenty-first Century: a New Generation Of Researchersmentioning
confidence: 99%